RUPTURES IN THE LIBRARY: THE NEOLIBERAL HIJACKING OF OPEN ACCESS - Steinberg, Reece; Pang, Matalie; Jacob, Arun; Lim, Elisha (AoIR Selected Papers of Internet Research, 2026)
This panel of librarians and internet researchers explains the dominant Open Access business model of academic publishing and why it must be rejected. The Big 5 academic commercial publishers, Wiley, Sage, Springer-Nature, Taylor & Francis and Elsevier, bury academic knowledge in a deep-web of paywalls and prohibitive subscriptions. Transformative Agreements have emerged as a major commercial model of transitioning journals from subscription to Open Access (OA) – mimicking movements like Open and Collectivized Data. This shift is often invisible to researchers, aside from learning that they are not required to pay Article Processing Charges (APCs) in order to publish OA. For researchers in regions requiring OA due to public grant stipulations, this seems like a boon, opening up the internet commons and bypassing APCs, which in some fields exceed 5000 USD. Open Access could be a way to make academic information and data findings free, but Transformative Agreements only offer technical OA status while introducing data use restrictions and prohibiting emerging and established research methods in data re-use. Worse, Transformative Agreements only boost elite and well-resourced institutions and the researchers fortunate enough to be affiliated with them. For new graduates, Global South researchers, publishing professionals outside of academia and many others, Transformative Agreements make research free to read but cause restrictions on publishing their own research. In the spirit of Web 2.0 corporate dominance, The Big 5 monopolize academic knowledge exchange and now with Transformative Agreements, leverage Open Data trends to further boost their commercial benefit. The first paper explains how we got here, from the expertise of a librarian whose responsibilities have included negotiating with vendors for university e-resources. Open Access started as a rejection of the online commercialization of academic knowledge by non-profit society and university publishers pushing back against the Big 5. However as researchers began to understand and cautiously embrace OA, publishers saw an opportunity for profit and began publishing hybrid OA journals, charging APCs to researchers and subscription fees to libraries – in effect “double dipping”. Simultaneously, publishers pushed libraries into purchasing “Big Deals” – large packages of journals instead of small collections or individual titles. Big Deals often consisted of a few essential journals and a long tail of niche and infrequently-used titles and became expensive and unpopular enough for libraries to fight back against them. This model also harmed relationships with researchers who understandably did not want to pay to publish. Big publishers claimed to their shareholders that individual consumers didn’t want to pay for anything digital, that library budgets were slimming and that their ability to grow by acquiring complements was faltering. Transformative Agreements were introduced as a corporate publisher solution, and sold to libraries as a transition phase on the journey to an Open future. The second paper discusses the meaning behind Open Access fragmented as green, gold, diamond and other variations of OA emerged thanks to advances in web publishing in the last two decades. The second author builds on Engestrom’s (1999) activity theory to argue that university libraries need to not lose sight of their role in supporting equitable access, but also equitable research production. This author discusses the implications of the different types of Open Access from the perspective of a representative and leader of libraries in Southeast Asia. The third paper explains how Transformative Agreements use Research Information Management Systems (RIMS) and networking platforms to further enrich academic journal publishers and their complementors. These publishers purportedly connect researchers with each other, with grants, and with impact factors, but exacerbate neoliberal optimization and extraction processes in universities, while funneling capital from universities to commercial enterprises. Author 3 builds on Brooke Erin Duffy and Jefferson Pooley’s analysis of Academia.edu to argue that learning analytics bring to light how universities are always-already invested in the enrichment of corporate wisdom through the optimization of data extraction processes and ever more expansive data procurement efforts (2017). In the fourth paper, a platform scholar asks, is this just a dying cry of an industry whose dominant companies missed out on platformization? Examining the trajectory of OA subscription models from a platform theory perspective, the industry seems outdated and clinging to models unlikely to work. As publishing companies are unable to convince content creators or customers of the value of their product, they turn to “orangewashing,” the academic ethics version of greenwashing, by calling their product Open Access. As internet researchers and librarians, we aim to share four different ways at looking at the problem of Transformative Agreements and how they affect and intertwine with internet research. We share our recommendations, and hope to use this panel to generate more.